Calmodulin permanently associates with rat olfactory CNG channels under native conditions - Bradley, Jonathan; Frings, Stephan (Nature neuroscience, 2004)
An important mechanism by which vertebrate olfactory sensory neurons rapidly adapt to odorants is feedback modulation of the Ca2+-permeable cyclic nucleotide−gated (CNG) transduction channels. Extensive heterologous studies of homomeric CNGA2 channels have led to a molecular model of channel modulation based on the binding of calcium-calmodulin to a site on the cytoplasmic amino terminus of CNGA2. Native rat olfactory CNG channels, however, are heteromeric complexes of three homologous but distinct subunits. Notably, in heteromeric channels, we found no role for CNGA2 in feedback modulation. Instead, an IQ-type calmodulin-binding site on CNGB1b and a similar but previously unidentified site on CNGA4 are necessary and sufficient. These sites seem to confer binding of Ca2+-free calmodulin (apocalmodulin), which is then poised to trigger inhibition of native channels in the presence of Ca2+.